Alexander disease: an astrocytopathy that produces a leukodystrophy - Sosunov, Alexander (Brain Pathol, 2018)
Alexander Disease (AxD) is a degenerative disorder caused by mutations in the GFAP gene, which encodes the major intermediate filament of astrocytes. As other cells in the CNS do not express GFAP, AxD is a primary astrocyte disease. Astrocytes acquire a large number of pathological features, including changes in morphology, the loss or diminution of a number of critical astrocyte functions and the activation of cell stress and inflammatory pathways. AxD is also characterized by white matter degeneration, a pathology that has led it to be included in the “leukodystrophies.” Furthermore, variable degrees of neuronal loss take place. Thus, the astrocyte pathology triggers alterations in other cell types. Here, we will review the neuropathology of AxD and discuss how a disease of astrocytes can lead to severe pathologies in non‐astrocytic cells. Our knowledge of the pathophysiology of AxD will also lead to a better understanding of how astrocytes interact with other CNS cells and how astrocytes in the gliosis that accompanies many neurological disorders can damage the function and survival of other cells.